2005
DOI: 10.1108/02652320510584412
|View full text |Cite
|
Sign up to set email alerts
|

Customer acceptance of internet banking in Estonia

Abstract: The Internet has emerged as one of the most important distribution channels for financial services firms. However, there is still a need to more fully understand the antecedents to customer use of banking via the Internet. The purpose of this article is to study technology acceptance of Internet banking in Estonia, an emerging east European economy. The present paper modifies the technology acceptance model and applies it to bank customers in Estonia, because Estonia, a country with a developing economy, has f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
244
6
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(282 citation statements)
references
References 61 publications
28
244
6
4
Order By: Relevance
“…Many of the researches supported that there is a positive and upward relationship between the perceived ease of use and the probability of adoption of internet banking (Wang, et al, 2003;Hernandez & Mazzon, 2007;Gounaris & Koritos, 2008). On the other hand, other researches (Pikkarainen et al, 2004;Eriksson et al, 2005) contradicted this result and concluded that the ease of use has no influence on the internet adoption.…”
Section: Independent Variablesmentioning
confidence: 70%
“…Many of the researches supported that there is a positive and upward relationship between the perceived ease of use and the probability of adoption of internet banking (Wang, et al, 2003;Hernandez & Mazzon, 2007;Gounaris & Koritos, 2008). On the other hand, other researches (Pikkarainen et al, 2004;Eriksson et al, 2005) contradicted this result and concluded that the ease of use has no influence on the internet adoption.…”
Section: Independent Variablesmentioning
confidence: 70%
“…computers, internet, etc. ), uncertainty such as security risks and trust; the service effectiveness and the knowledge about transferring online (Eriksson et al, 2005;Yousafzai, 2012;Kuisma et al, 2007). Therefore, it becomes imperative for bank managers and policy makers to understand the factors that can hinder or facilitate the acceptance and usage of IB which enable them to formulate strategies to improve the take up of IB.…”
Section: Ali Tarhinimentioning
confidence: 99%
“…In Lebanon, the number of internet users increased from 13.3 to 80.4 per cent of the population between 2005(Internet World Stats, 2014 which created opportunities for Lebanese banks to expend to wider customers. However, despite the relatively advanced and well-managed banking system and the huge amount of money and resources that have been projected in this vein by all Lebanese banks (approximately $150 million were invested to implement the IB services) (Association of Banks in Lebanon, 2013), online banking is still a relatively new phenomenon in Lebanon and its adoption by the customers is reported to be very low (Itani, 2008).…”
Section: Ali Tarhinimentioning
confidence: 99%
“…It has been recommended by the results of this study that the determinants of service quality provide the basis of customer satisfaction. It has been exposed that while making 5 Polatoglu and Ekin (2001), Eriksson et al, (2005), Musiime and Ramadhan (2011) 6 Sathye (1999), Al Hajri (2008. 7 Jun and Cai (2001), Rod et al, (2009), Nupur (2010 8 Raza and Hanif (2013) enhancements in the satisfaction level of customers, the managers are required to appropriately weight the core performance, features and relative performance factors in context of retail banking.…”
Section: Introductionmentioning
confidence: 99%